ADR as an alternative access to justice in resolving WAQF land disputes - Abdul Manaf, Zati Ilham; Syed Abdul Kader, Sharifah Zubaidah; Mohamad, Nor Asiah (CLJ Legal Network Sdn Bhd, 2018)
The development of Waqf lands in Malaysia is steadily growing and has attracted the interest of many. States in Malaysia are beginning to promulgate their own Waqf enactments therefore granting their State Islamic Religious Council (SIRC) more power in administering and managing Waqf lands. Coupled with the call for a more effective method of registration and for the introduction of a Waqf registry, the administration of Waqf lands in Malaysia holds a promising future. The issue regarding management of disputes however remains as one of the lingering issues which hamper the development of this promising institution. A survey of surrounding literature shows that most of the Waqf related disputes brought to court relates to the question of validity of the Waqf land as well as the management of Waqf land by the SIRC as trustees. Coupled with questions of jurisdiction between the Shariah and civil courts, cases involving Waqf are usually exposed to extensive delays which in effect incur exorbitant costs for the parties involved. This has put the State Religious Council (SIRC) in a dilemma in pursuing any Waqf related disputes. Therefore, by adopting the qualitative approach, the paper analysed reported cases involving Waqf lands in Malaysia and literature on ADR and Waqf to determine the best way forward to address this issue. It is felt that the utilization of ADR processes should be considered as a viable solution to this problem.